Exosome‐shuttled mitochondrial transcription factor A mRNA promotes the osteogenesis of dental pulp stem cells through mitochondrial oxidative phosphorylation activation. Issue 12 (26th August 2022) - Guo, Jia; Zhou, Feng; Liu, Zhi; Cao, Yuan; Zhao, Wanming; Zhang, Zheru; Zhai, Qiming; Jin, Yan; Li, Bei; Jin, Fang
Abstract: Objectives: The treatment of bone defects by stem cells (MSCs) has achieved limited success over the recent few decades. The emergence of exosomes provides a new strategy for bone regeneration. Here, we aimed to investigate the effect and mechanisms of exosomes combined with dental pulp stem cells (DPSCs) on bone regeneration. Materials and Methods: We isolated exosomes from stem cells from human exfoliated deciduous teeth (SHED) aggregates and evaluated the efficacy of exosomes combined with DPSCs in a cranial bone defect model. The potential mechanisms were further investigated. Results: The effect of exosomes combined with DPSCs was remarkable on bone regeneration in vivo and exosomes promoted osteogenic differentiation of DPSCs in vitro. Mechanistically, exosomes increased the expression of mitochondrial transcription factor A (TFAM) in DPSCs by transferring TFAM mRNA. Moreover, highly expressed TFAM in DPSCs enhanced glutamate metabolism and oxidative phosphorylation (OXPHOS) activity. Conclusions: Consequently, exosomes strengthened bone regeneration of DPSCs through the activation of mitochondrial aerobic metabolism. Our study provides a new potential strategy to improve DPSC‐based bone regenerative treatment. Abstract : Exosomes increase mitochondrial transcription factor A (TFAM) expression in DPSCs by transferring TFAM mRNA. Moreover, highly expressed TFAM in DPSCs enhances GDH expression and OXPHOS activity. Meanwhile, glutamate metabolism provides amounts of NADH to OXPHOS. Consequently, exosomes strengthen osteogenic differentiation of DPSCs through the activation of mitochondrial aerobic metabolism.